Granitoid related Sn-W mineralisation with special reference to southern Africa, the Variscan Belt in Europe, and the Malay Peninsula - Bentley, Philip Nelson (Rhodes University, Faculty of Science, Department of Geology, 1985)
A review of the geotectonic settings of granitoids and various tin-tungsten provinces in Europe, Malaysia and southern Africa shows a close spatial and temporal association of mineralisation to S-type ilmenite series granitoids. Granitoids with these affinities are derived from crustal anatexis and are most commonly found in continental collision and different ensialic, intraplate orogenic settings, (e.g. SW England, Malaysia, Namibia) as well as in association with anorogenic magmatism (Nigeria, Brazil, South Africa). Tin-tungsten mineralisation is related to late- to post-tectonic granites, emplaced into areas of substantial tectonic thickening. Crustal anatexis leads to an observable calcalkaline chemical trend, with a source of gabbroic or amphibolite composition through anatexis to; mafic-intermediate enclaves, para-autochthonous anatectic granitoids (tonalite, granodiorite), to intermediate level quartz monzonite, granodiorite, biotite-granite, to late-tectonic highly fractionated muscovite-bearing granites, and high level porphyry intrusions. Mineralisation is spatially related to apical protrusions of the youngest most differentiated granite. Various mineralised environments are recognised, including endogranitic veins, primary disseminations, pegmatites and pipes, and exogranitic stockwork and fissure veins, and replacement bodies. A common factor to all these deposits is the inherent greisen environment, characterised by postmagmatic metasomatic alteration and mineral deposition. Common alteration mineral assemblages include albite, quartz, muscovite, tourmaline, and fluorite âˆ“ topaz. Ore mineral assemblages commonly display a paragenetic sequence of oxides (cassiterite, wolframite, scheelite), followed by sulphides (molybdenite, pyrite, pyrrhotite, chalcopyrite sphalerite, arsenopyrite/loëllingite, Pb-Bi(Ag) sulphosalts) and then lower temperature carbonates (calcite, siderite, ankerite). Analysis of Pan African orogenic provinces in southern Africa (Damara and Saldanian Provinces) shows there is good potential for applying integrated exploration techniques in search of endo-exogreisen Sn-W systems. Careful analysis and interpretation of granitoid geochemistry (Kâ‚‚0, Naâ‚‚0, FeO/Feâ‚‚0â‚ƒ, F, B, Sn, W, Mo, Cu, Rb, Sr, Ti, Zr) should aid delineation of Sn-W and Mo-Cu metallogenic provinces in these regions. Magnetic susceptibility determinations should also aid distinction of S-type ilmenite series (less than 1 x lOâ »â ´emu/g ) from I-type magnetite series (more than 1 x lOâ »â ´emu/g ) granitoids
Keywords: Geotectonic settings; Granitoids; Granites; Tin-tungsten; Mineralisation; Greisen environment; Minerals; Exploration